MTA-Based Root Canal Sealers - Rawtiya, Manjusha; Verma, Kavita; Singh, Shweta; Munuga, Swapna; Khan, Sheeba (Journal of Orofacial Research, 2013)
Mineral trioxide aggregate (MTA) has been recommended for pulp capping, pulpotomy, apical barrier formation in teeth with open apexes, repair of root perforation and root canal obturation. Since, its introduction in 1993 by Torabinejad numerous studies have been published regarding various aspects of this material. The aim of this review was to consider MTA as root canal sealer and various laboratory experiments and clinical studies of MTAbased root canal sealers. An extensive search of the endodontic  literature was made to identify publications related to MTA-based root canal sealers. The articles were assessed for the outcome of laboratory and clinical studies on their biological properties and physical characteristics. Comparative studies with other sealers were also considered. Several studies were evaluated covering different properties of MTA-based sealers includingphysical properties, biocompatibility, leakage, adhesion, solubility, antibacterial properties and periapical healing effect. Comparative studies reveal their mild cytotoxicity, but theirantibacterial effects are variable. Further research is required to establish the role of MTA as root canal sealers.